The First Variety of Tumba: ‘Mansha Marudhara’ (‘RMT 59’) released - Raiger, H L; Dua, R P; Sharma, S K; Phogat, B S; Bhandari, M M C (Indian Farming, 2015)
This is first variety of tumba which is superior for seed yield andfruit yield. The variety is characterized by wide adaptability indesert and arid condition and resistant to major disease, insect andpest. It has average seed yield of 2.57 q/ha. The fruits are globular, variegated, green, mottled with yellowish blotches, arranged in undulating bands, yellow with pale white yellow rays emanating from base to apex with some greenish patches when fruits are young and yellow on maturity.